(untitled) (Diametros, 2014)
The aim of this paper is to present two arguments against the dialectical interpretation of Nagarjuna’s philosophy. This interpretation understands Nagarjuna’s philosophy as a method of deconstruction, abstracting from Nagarjuna’s own standpoint. The first argument refers to the metaphysical presuppositions of this method. The second argument refers to the positive statements asserted by Nagarjuna and focuses mainly on those concerning Buddhist practice. Furthermore, the conception of ’skillful means’ and ’the two truths’ will be discussed. The conclusion of this paper is that Nagarjuna’s philosophy is based upon determining the conditions of the possibility of the Buddhist practice rather than on a dialectic without any metaphysical assumptions.